Do salvamento marítimo - Barreira, Henrique Sanhudo (2022)
Two-thirds of our planet are covered by the sea, an important source of resources and a privileged way of circulation. The trading growth, the increase of people living in coastal cities, the extension of the Portuguese continental platform, boost the regulation needs as to what concerns the maritime area, and entails the constant need of awareness on surveillance and maritime rescue matters. The maritime security is, not only a national task, but an international concern, as can be easily seen by the variety of supranational diplomas. With the occurrence of maritime accidents, not only Portugal, but the international community got aware of the need for preventing and mitigating its effects. For such, there were made efforts to create mechanisms and international legal instruments to harmonize maritime safety and security procedures, product of a constant evolution. The mottoes are: prevent, search, rescue, research and analyze the maritime accidents, so that the Countries can be able to undertake effective procedures. Where did we came from? What will the future bring?